Withholding vs. Continuing Angiotensin-Converting Enzyme Inhibitors or Angiotensin Receptor Blockers Before Non-cardiac Surgery in Older Patients: Study Protocol for a Multicenter Randomized Controlled Trial - Yang, Yu-fan; Zhu, Ya-juan; Long, Yu-qin; Liu, Hua-yue; Shan, Xi-sheng; Feng, Xiao-mei; Peng, Ke; Ji, Fu-hai (Frontiers in Medicine, 2021)
Background: Older hypertensive adults are at increased risk for postoperative morbidity and mortality. As first line antihypertensive drug therapy, angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) have many beneficial effects. However, the use of ACEIs/ARBs in the perioperative period remains controversial. This study aims to determine the effects of withholding versus continuing ACEIs/ARBs before noncardiac surgery on perioperative hypotension and postoperative outcomes in older patients. Methods: In this multicenter, randomized, double-blind, placebo-controlled trial, a total of 2036 patients aged 60–80 years undergoing noncardiac surgical procedures will be randomly assigned, in a 1:1 ratio, to receive oral ACEIs/ARBs (the ACEIs/ARBs continued group) or inactive placebos (the ACEIs/ARBs withheld group) on the morning of surgery. For both groups, the ACEIs/ARBs will be continued from the first postoperative day. The primary outcome measure is the incidence of perioperative hypotensive events, defined as mean blood pressure (MBP) < 65 mmHg or ≥ 30% reduction in MBP from baseline during surgery and in a post-anesthesia care unit. The secondary outcomes include duration of perioperative hypotension, intraoperative use of fluids and vasopressors, hypotensive events within postoperative 3 days, and perioperative neurocognitive disorders, major adverse cardiocerebral events (a composite outcome of stroke, coma, myocardial infarction, heart block, and cardiac arrest), and mortality within 30 days after surgery. Discussion: The results of this trial will offer an evidence-based perioperative ACEIs/ARBs therapy for older hypertensive adults undergoing noncardiac surgery. Study Registration: This study is approved by the Medical Ethics Committee of The First Affiliated Hospital of Soochow University (Approval No. 2020-077-1) and by the institutional ethics review board of each participating center. This protocol is registered at the Chinese Clinical Trials Registry (ChiCTR2000039376).